Walden or the Violence of the Letter: Toward a Theory of Reading - Isabelle Alfandary (Sillages Critiques)
This article seeks to unfold and contemplate the terms, conditions and consequences of Walden’s groundbreaking theory of reading based on an understanding of the sign as original if not originary, leading to an inversion of the values of sound and echo, presence and absence, reading and literature, mother tongue and writing.